A study of Azadamard :|socialism and the Armenian Revolutionary Federation's understanding of Socialist Ottomanism - Yalçın, Orhun. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis examines the policies of the ARF through the articles published by the Azadamard newspaper, the publishing organ of the Armenian Revolutionary Federation, between March 1911 and September 1912. I argue that the Armenian Revolutionary Federation had a policy that could be called Socialist Ottomanism after the 1908 Constitutional Revolution. The ARF’s understanding of socialism is quite interesting because, before the 1908 Constitutional Revolution, it had a revolutionary armed struggle view with the influence of the Russian Narodniks, which was intertwined with nationalist ideas, but after the 1908 Constitutional Revolution, it adopted a policy closer to the European reformist socialists, and the policy of ‘Ottomanization’ replaced the influence of Armenian nationalism. Therefore, it will first examine the socialist movements in the Ottoman Empire and the policies of the ARF before the 1908 Constitutional Revolution. And then, through the articles in the Azadamard newspaper, the ARF’s views on the government, the function of the parliament, the follow-up of the promises before the revolution, on the Kurds and their land reform demands within the framework of the Socialist Ottomanism will be evaluated.|Keywords : the Armenian Revolutionary Party, socialism, Azadamard, Socialist Ottomanism, the Ottoman Empire, 1908 Constitutional Revolution
Keywords: Armenian newspapers -- Turkey -- Istanbul.